TRIPARTISM AS THE FACTOR OF DEVELOPMENT OF THE HIGHER SCHOOL (BY THE EXAMPLE OF THE VOLGA STATE UNIVERSITY OF TECHNOLOGY) - Romanov, Evgenii; Andrianov, Yurii; Nizova, Lyudmila; Sannikova, Tatyana (Journal of Applied Engineering Science, 2017)
The role of the International Labour Organization as the center of social partnership with the reasoning of Conventions and Recommendations, development of tripartism in the countries of Europe, the USA and Japan is revealed. By the example of genesis of partner relations in the Russian Federation, the authors describe institutional environment including formal and informal institutes under conditions of economic, social, legal, political and demographic factors influencing them. On the basis of monitoring, the priorities of positive influence of social partnership on the development of the sphere of education and science, both on republican, and on corporate levels are determined. Higher school became a special area of research, the Volga State University of Technology, as its representative member, bases its pioneering work on a versatile activity of the Guardian council. Significant proof of the efficiency of its influence is training and employment of the engineering staff.